Larangan Riba dan Relevansinya terhadap Praktik Keuangan Syari’ah Indonesia Menurut Tafsir Qs. Al-Baqoroh - Siti Nur Julianti; Rizka Mahardika; Chofifah Wahyu Hidayah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the concept of the prohibition of riba in QS. Al-Baqarah verses 275–279 and examine its relevance to the practice of Islamic finance in Indonesia. The focus of the study is directed toward understanding the meaning of riba according to classical and contemporary tafsir scholars, the theological foundation of its prohibition, and the implementation of anti-riba principles within the modern Islamic financial system. The research also seeks to explain how Qur’anic values are translated into regulations, financial products, and operational mechanisms of Islamic financial institutions in Indonesia. The research employs a qualitative library-based method. Data were collected through the review of Qur’anic verses, classical and modern tafsir works, Islamic economic literature, and Islamic finance regulations such as DSN-MUI fatwas and OJK guidelines. The data were analyzed using a descriptive-analytical approach to identify the relationship between the concept of riba prohibition and the practices of Islamic finance. The findings indicate that riba is understood as an additional charge required beyond the loan principal without productive activity, which leads to injustice and exploitation. Tafsir scholars affirm that the prohibition of riba aims to uphold economic balance and fairness. The study also reveals that anti-riba principles have been practically implemented in Indonesia’s Islamic financial system through the use of permissible contractual structures, profit-sharing mechanisms, asset-based financing, and Islamic capital market instruments such as sukuk. The study concludes that the prohibition of riba is not only theological in nature but also highly relevant in practice. These Qur’anic principles have successfully become the foundation for the development of a more just, transparent, and welfare-oriented Islamic financial system